Analisis ANALISIS SUMBER DAN PENGGUNAAN DANA KAMPANYE DIGITAL PRABOWO SUBIANTO DAN GIBRAN RAKABUMING RAKA PADA PEMILIHAN UMUM 2024: ANALYSIS OF SOURCES AND USES OF DIGITAL CAMPAIGN FUNDS OF PRABOWO SUBIANTO AND GIBRAN RAKABUMING RAKA IN THE 2024 GENERAL ELECTION - Rafif, Faiz Akmal Rafif; Maria, Angelica; Zuniati, Annisa Risky (Journal of Social Contemplativa, 2025)
In the context of electoral politics, campaign finance plays an important role in determining the success strategy of the campaign and shows the extent of transparency of each candidate pair. Prabowo Subianto-Gibran Rakabuming Raka's victory in the 2024 General Election shows that they managed to use campaign funds effectively to gain significant vote support reaching 58%. This research aims to dig deeper into the sources of campaign funds obtained by Prabowo and Gibran and how they were used in the 2024 General Election campaign. The research method used by the author is a qualitative method with literature study collection techniques. From the analysis, the author concluded that the Prabowo Subianto-Gibran Rakabuming Raka pair had a campaign fund source of Rp 207 billion. The funds came from various sources, including individual donations, political party funds, donations of goods and services, as well as contributions from companies and non-governmental bodies. Their campaign was supported by an intensive strategy on social media that succeeded in building an image as a firm and authoritative leader. This success was reflected in significant vote gains, particularly in West Java where the pair won 58% of the vote. A large investment of more than Rp28.6 billion in digital advertising also proved to be a key factor in gaining widespread support from the public.